2020
DOI: 10.1038/s41598-020-74918-9
|View full text |Cite
|
Sign up to set email alerts
|

NGS-based barcoding with mini-COI gene target is useful for pet food market surveys aimed at mislabelling detection

Abstract: Pet food industry has grown considerably in the last few years and it is expected to continue with this rate. Despite the economic impact of this sector and the consumer concerns for the increasing number of food and feed adulteration cases, few studies have been published on mislabelling in pet foods. We therefore investigated the capability of a next generation sequencing-based mini-barcoding approach to identify animal species in pet food products. In a preliminary analysis, a 127 bp fragment of the COI gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 51 publications
(62 reference statements)
1
5
0
Order By: Relevance
“…The studies of Dunham-Cheatham et al [25] have shown that adulteration is common in commercial pet food. This fact is confirmed by the analyzes of Palumbo et al [24] who found that 16 of 18 commercial pet foods tested were adulterated. Both studies have shown that ingredients with higher economic value (e. g. fish) are often supplemented or completely replaced with ingredients with lower economic value (e. g. chicken).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The studies of Dunham-Cheatham et al [25] have shown that adulteration is common in commercial pet food. This fact is confirmed by the analyzes of Palumbo et al [24] who found that 16 of 18 commercial pet foods tested were adulterated. Both studies have shown that ingredients with higher economic value (e. g. fish) are often supplemented or completely replaced with ingredients with lower economic value (e. g. chicken).…”
Section: Discussionsupporting
confidence: 56%
“…In recent years, many techniques have been developed to allow food traceability through DNA barcoding techniques even for complex and highly processed mixtures such as pet food. These techniques can identify adulteration in pet food products, which are an increasing problem among consumers and underpin several lawsuits in recent years [23,24]. Properly selected methods can also provide a way to confirm that pet food is indeed "grain free", "corn free" or "chicken free" for example, claims that are becoming more common in many commercial pet products [25].…”
Section: Discussionmentioning
confidence: 99%
“…In order to exclude very short sequences, nuclear genomes and genomic scaffolds, only sequence lengths ranging from 100 bp to 60 kbp were considered (the latter being the approximate length of the longest mitochondrial genome reported to date ( 26 )). The selected short fragments (less than 500 bp) would potentially benefit the experiments based on DNA mini-barcodes ( 27 , 28 ) or on reads of typical HTS outputs ( 29 ). To avoid the presence of stop codons and to increase the accuracy of matching with the reference COXI profile, all DNA sequences were translated into amino acids, with a custom python script (newTranslator_CExtract.py), using their corresponding mitochondrial genetic code (retrieved from NCBI taxonomy dump files: https://www.ncbi.nlm.nih.gov/taxonomy ) and all six open reading frames.…”
Section: Methodsmentioning
confidence: 99%
“…Thank to these new generation of sequencers, all the DNA molecules extracted from the matrices can be simultaneously amplified and sequenced allowing species identification also in complex foods containing multiple ingredients. Although application of metabarcoding to trace ingredients is still in its infancy, several studies have tested this approach for species identification in different food products including dairy (Ribani et al, 2018), seafood (Giusti et al, 2017;, commercial plant (Bruno et al, 2019), herbal medicinal (Anthoons et al, 2021), candies (Muñoz-Colmenero et al, 2017) honey (Prosser & Hebert, 2017;Wirta et al, 2021), probiotics (Patro et al, 2016) and pet food (Palumbo et al, 2020;Preckel et al, 2021). Few studies applied metabarcoding to investigate the species composition in artificially prepared mixtures or commercial meat and meat products (i.e., sausages, balls, canned luncheon meat, minced meats, kebab) made of several animal species including beef, camel, horse, sheep, deer, swine and/or poultry (Cottenet et al, 2020;Dobrovolny et al, 2019;Pan et al, 2020;Preckel et al, 2021;Xing et al, 2019).…”
Section: Introductionmentioning
confidence: 99%